The use of alcoholic liquors: economically, socially, and morally wrong - Haughton, James (Statistical and Social Inquiry Society of Ireland, 1849)
In a former paper which I had the honour to read before this society, I showed the intimate connexion between intemperance and crime. I purpose, on the present occasion, to carry out the object I then had in view, and to occupy your attention by a brief examination of the evils which result to society, in an economic, a social, and a moral point of view, from the use of alcoholic liquors. The inquiry will include an investigation into the consequences resulting to mankind, in relation to their wealth, their health, and their happiness, from this cause.
Read May 21st 1849
Keywords: Alcohol use; Death rate; 314.15